Employees Perspectives On Performance Management In A Singapore Public Healthcare Institution - Koh, Paulin (2007)
Performance Management (PM) is the strategic and integrated process that delivers sustained success to organisations by improving the performance of people who work in them and by developing the capabilities of individual contributors and teams. Faced with a competitive business environment, public healthcare institutions are under relentless pressure to demonstrate improvements in performance of business objectives. This has made it imperative for effective PM approaches to be developed and applied. Current research has revealed a wealth of information on fundamentals of human resource management (HRM) theories and HRM and PM practices; but greater understanding is required on how employees think and embrace the practices.